Development of efficient semipolar InGaN long wavelength light-emitting diodes and blue laser diodes grown on a high quality semipolar GaN/sapphire template. (28th May 2020) - Li, Hongjian; Zhang, Haojun; Li, Panpan; Wong, Matthew S; Chow, Yi Chao; Pinna, Sergio; Klamkin, Jonathan; DeMierry, Philippe; Speck, James S; Nakamura, Shuji; DenBaars, Steven P
Abstract: Semipolar/nonpolar GaN-based optoelectronic devices become attractive due to several advantages such as alleviation of quantum-confinement Stark effect, high polarization ratio and optical gain. High performance semipolar/nonpolar InGaN light-emitting diodes (LEDs) and laser diodes (LDs) grown on semipolar/nonpolar bulk GaN substrate have been demonstrated. Owing to the limited size of such costly substrate, hetero-epitaxial growth of semipolar/nonpolar LEDs and LDs on foreign substrate causes lots of attentions. However, it is very challenging to realize efficient semipolar/nonpolar optoelectronic devices on foreign substrate due to the high dislocation density and possibly high basal plane stacking fault density. In this article, we review two growth methods to obtain high crystal quality semipolar (11-22) and (20-21) GaN layers on specially patterned sapphire substrate. The use of these substrates leads to the realization of efficient long wavelength InGaN semipolar LEDs and the first demonstration of semipolar blue LDs grown on foreign substrate shown in our previous reports. These results demonstrate significant progress in exploring the semipolar GaN materials quality and the devices efficiency grown on foreign substrate.